Pengaruh Kepemimpinan dan Motivasi Terhadap Kualitas Kerja Pegawai pada Kantor Pengawasan dan Pelayanan Bea dan Cukai Tipe Madya Pabean B Medan - Fransdarmehta Januardani . (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
This study is aimed at finding out the influence of leadership and motivation on employee performance at the Customs and Excise Supervision and Service Office Type B Medan Customs. The research population was employees of the Customs and Excise Supervision and Service Office, Middle Type Customs B, Medan customs and excise section, totaling 32 (thirty two) employees. All members of the population are sampled. The sample in this study was the entire population of 32 (thirty two) employees. Data was obtained by conducting interviews using a questionnaire. The research results show that the leadership and motivation variables have a significant effect, both partially and simultaneously, on the work quality variable as indicated by a sig value <0.05.